IMPLIMENTASI SENI DALAM PENDIDIKAN KARAKTER SEBUAH ALTERNATIF MENUJU KEDAMAIAN (LPPM IKIP PGRI Bali, 2019)
To fokcus on the achievement objectives in this study there are twoproblems, namely : (1) to know anddesciribe the volue of character sducation in the learning of Indonesien dance, especialy music as an accompaniment of performing art. This study,  descptive research that prioritizes collecting data through ?tri anggulasi?; valid experience,intervews and literature with this research. The method of analyzing data is a descriptive method of analisys.           Based on the results of data analisys, it isexpected that in conlusion that artgenerally contains many character education volues cntainedin it that are in accordance with the Enghteen disciplined, hard work, creative,indenpedent, demockratic, curiocity, spirit of pride, love of waterresistance, repect forachievenment, communicative,  peace-loving,fond of reading,caring for the environment, caring for the cocial and responsibility,then art can provide specific material to environment, caring for the social and responscibility, then trough art can provide specific materialto student, so theycan olso realized it significantly.